2021
DOI: 10.1101/2021.06.17.21257667
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“It’s hard to keep a distance when you’re with someone you really care about” — a qualitative study of adolescents’ pandemic-related health literacy and how Covid-19 affects their lives

Abstract: Purpose The aim of this study was to explore how adolescents accessed, understood, appraised, and applied information on pandemic preventive measures, how their lives were impacted by long-lasting regulations and how they described their quality of life. Methods A qualitative design with focus group interviews was used to elaborate on the quantitative survey results obtained and analyzed in a previous survey study from the first phase of the Covid-19 pandemic. Five focus groups with seventeen adolescents wer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…For those who are still in education or transitioning to working life, the pandemic has led to an interruption of education and employment biographies ( 51 ). As the pandemic progresses and economic problems increase, studies reveal growing fears among young people regarding learning outcomes and prospects ( 52 , 53 ). Unemployment rates for young people under 25 in Austria were almost twice as high as in the general population in February 2022 ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…For those who are still in education or transitioning to working life, the pandemic has led to an interruption of education and employment biographies ( 51 ). As the pandemic progresses and economic problems increase, studies reveal growing fears among young people regarding learning outcomes and prospects ( 52 , 53 ). Unemployment rates for young people under 25 in Austria were almost twice as high as in the general population in February 2022 ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…As such, it seems that although school closures and restrictions likely play a role in mental health [ 19 , 20 ], more general pandemic factors are also involved, such as rises in daily COVID cases [ 37 ], slow vaccination rates in Austria, exhaustion/depletion of mental resources [ 41 ], and concerns about the future [ 4 ]. These are in addition to the non-pandemic mental health challenges already faced by adolescents, particularly girls [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although mental health symptoms remained poor in comparison to the available pre-pandemic data, a small improvement was observed in June/July compared to February [ 19 ]. In line with this, Riiser et al [ 20 ] found that well-being depended on the magnitude of restrictions and children reported the challenges of distance learning and school as an important place for socializing as well as learning ([ 21 ], but see [ 22 ]).…”
Section: Introductionmentioning
confidence: 93%